Interior Cafe Jamu Tradisional Jawa di Surabaya - Effendy, Mella Nilasari (Intra, 2014)
In Java, there are various brands of herbal medicine that has been growing rapidly. Interior design of traditional herbal java cafe is a commercial design in Surabaya. This includes information cafe area, kitchen area, shop area, office area, staff areas and toilets. The purpose of this design is to design a cafe which added informative value and can attract visitors that will come back again to enjoy the product as well as the interior. The concept of design is healthy, this concept taken from the purpose of the herbal medicine itself which is to nourish the body. Generally this concept was applied to simple and organic formation furniture, using dominant natural material, circulation between floors using a ramp, maximizing the use of natural lighting, and pay attention to inddor air quality.